Estudo do comportamento de barras compostas comprimidas formadas por perfis tubulares circulares concêntricos laminados de aço - Lucas Figueiredo Grilo (2015)
This research presents a study of the compression behavior of built-up members composed of concentric hot rolled circular hollow sections. The use of these composed bars is an innovative solution of practical interest for situations in which a single bar does not reach the required compressive strength. This work presents a review of the elastic buckling behavior of isolated bars, the influence of geometric and physical imperfection and the plastic hinge formation when the bar instability occurs. The current compressive strength formulation for circular hollow steel sections profiles according to European, American, Canadian and Brazilian Standards were presented and compared. An analytical model was developed to estimate the compressive strength in tubular steel sections, with any initial crookedness, and compared to the Standard ABNT NBR 16239:2013. This analytical formulation can be used in isolated and composed bars. Some technically and economically viable design and fabrication solutions to built-up members composed of concentric hot rolled circular hollow sections are presented. For validation of numerical results, models of singular hollow sections are made and compared to the ABNT NBR 16239:2013 Standard results. The results obtained with numerical models were satisfactory. The compressive strength of these numerical models differs less than 6,5% of the Brazilian Standard values. Once the numerical modeling was validated, the study of built-up members was made, considering three different types of connections between the tubes: fixed connection, sliding connection and without any connections along the bars. Several models of built-up sections were simulated, in order to obtain and compare the various compressive resistance curves of each connection. The numerical results show that these built-up sections with fixed and sliding connections have a very similar behavior to the results obtained with Brazilian Standard formulation, when considering equivalent areas and inertias for the built-up section. Also, it shows that this observation does not apply to the sections without connections. Comparative graphs of the compressive resistance curves were generated, as also some graphs that show the distribution of the compressive force between each bar of the built-up section. Finally, a simplified formulation for the design of built-up sections without connections along the tubes was proposed, in order to avoid robust computational methods.